Hollow Cathode Plasma (HCP) Enhanced Atomic Layer Deposition of Silicon Nitride (SiNx) Thin Films Using Pentachlorodisilane (PCDS). (23rd April 2019) - Hwang, Su Min; Kondusamy, Aswin L. N.; Qin, Zhiyang; Kim, Harrison Sejoon; Meng, Xin; Kim, Jiyoung; Hwang, Byung Keun; Zhou, Xiaobing; Telgenhoff, Michael; Young, Jeanette
Abstract : In this work, effects of NH3 /N2 and N2 -H2 /Ar plasma gases for the growth of PEALD SiNx films using pentachlorodisilane (PCDS, HSi2 Cl5 ) were studied using a hollow cathode PEALD system. At identical process conditions, the combination of PCDS and N2 −H2 /Ar plasma showed a relatively lower (approximately < 10 %) growth rate as compared to NH3 /N2 plasma under a range of process temperatures (240−300 °C) whereas the wet etch resistance to HF acid was improved (> 1.6 nm/min, 500:1 HF). Using XPS and FTIR analysis, it was identified that N2 −H2 /Ar gas mixture results in a Si-rich SiNx film with less N−Hx bonds when compared to NH3 /N2 mixture, thereby resulting in a decreased wet etch rate.